Preparation of Chloro Penta Amine Cobalt(III) Chloride and Study of Its Influence on the Structural and Some Optical Properties of Polyvinyl Acetate - Nada K. Abbas; Majeed Ali Habeeb; Alaa J. Kadham Algidsawi (International Journal of Polymer Science)
Chloro penta amine cobalt(III) cloride [Co(NH3)5Cl]Cl2 was prepared and then characterized by Fourier transform infrared spectroscopy and X-ray diffraction. The obtained results indicated the formation of orthorhombic [Co(NH3)5Cl]Cl2 nanoparticles of ≈28.75 nm size. Polymeric films based on polyvinyl acetate (PVAc) doped with chloro penta amine cobalt(III) cloride [Co(NH3)5Cl]Cl2 in different weight percent ratios were prepared using the solvent cast technique. The complexation of the additive with the polymer was confirmed by FTIR and SEM studies. The XRD pattern revealed that the amorphousicity of PVAc polymer matrix increased with raising the [Co(NH3)5Cl]Cl2 content. Parameters such as extinction coefficient, refractive index, real and imaginary parts, and optical conductivity were studied by using the absorbance and measurements from computerized UV-visible spectrophotometer in the spectral range 190–800 nm. This study showed that the optical properties of PVAc were affected by the doping of [Co(NH3)5Cl]Cl2 where the absorption increased by leveling up [Co(NH3)5Cl]Cl2 concentration. The nature of electronic transition from valence band to conduction band was determined and the energy band gaps of the composite films samples were estimated by UV-visible spectrum. It was observed that the optical conductivity increased with photon energy and with the increase of [Co(NH3)5Cl]Cl2 concentration.